Effect of Regular Sports Activity in the Salivary Glands in Short and Long Distance Sprinters for Track and Field Games - Hayder Flayyih Hasan (Journal of Global Pharma Technology, 2018)
Saliva is produced in salivary gland and the human saliva consists of 99.5% water but contains many important substances such as electrolytes. Mucus antibodies to bacteria and various organisms. This study was studied by enzymes which are biological catalysts of different chemical structures. And affect the speed of some reactions without consumption. The importance of this research lies in the role of these enzymes, which are studied in the health of teeth and mouth “isosomiee, hactoferin, Bromine, globin alga” and the percentage of the concentration of these enzymes. Which are of the quantity and quality of saliva produced from the salivary glands? The latter is an acquired by adapting the activity of the sports activity with the training intensity. Such as long - term diseases of the field work of these glands in secretion is very important in the durability of motor performance such as sports activities. By moisturizing the mouth and facilitating the process of breathing and swallow saliva especially that such sports activities rely on the energy … so the study assumes that the long-distance runners have a quality and the amount of salivary secretion useful more than short- distance runners during periods of rest or practice of normal daily life because the saliva of the mouth decreases during the exercise of violent physical exercise this necessarily means that long - distance sprinters enjoy the health of teeth and mouth over short runners to contain their saliva on an enzymatic con centration.Keywords: Regular sports, salivary glands, short and long distance and sprinters.